Overexpression of NPTX2 Promotes Malignant Phenotype of Epithelial Ovarian Carcinoma via IL6-JAK2/STAT3 Signaling Pathway Under Hypoxia - Han, Xiaotian; Lu, Yechen; Li, Xiaoqi; Xia, Lingfang; Wen, Hao; Feng, Zheng; Ju, Xingzhu; Chen, Xiaojun; Wu, Xiaohua (Frontiers in Oncology, 2021)
Background: Epithelial ovarian cancer(EOC) is the main subtype of ovarian cancer and shows an aggressive phenotype and poor prognosis. Neuronal pentraxin II (NPTX2) is a member of the neuronal pentraxin family and plays a contradictory role in different tumors. However, there has been no report about the possible role and effect of NPTX2 in EOC. Methods: Bioinformatics analysis, qPCR, western blotting and immunohistochemistry were used to detect the expression of NPTX2 in EOC. Lentivirus-based transfection for NPTX2 overexpression or knockdown was performed on the EOC cell lines A2780, HEY, SKOV3 and OVCAR-3. The effect of NPTX2 on the malignant phenotype of EOC was examined through methods of MTS assay, Edu assay, transwell assay, western blotting analysis, qPCR analysis, luciferase reporter assay and xenograft experiment. Results: EOC tissues showed higher NPTX2 expression than the normal tissues with poor prognosis. NPTX2 overexpression can promote the proliferation, invasion, migration and tumorigenesis of EOC via IL6-JAK2/STAT3 signaling pathway. Moreover, hypoxia-inducible factor-1(HIF-1) can promote the transcription and expression of NPTX2 under the hypoxic environment. NPTX2 knockdown abolished the hypoxia-induced malignant phenotypes in ECO. Conclusions: The above results suggest that NPTX2 may play a novel role in ovarian cancer's malignant phenotype and act as a promising treatment target for EOC molecular therapy.